Impact of livelihood practices on the char dwellers economic condition in riverine chars: Case studies in Bangladesh - Rahman, Mohammad Arifur; Rahman, Md Munsur (Journal of the Bangladesh Association of Young Researchers, 2011)
The present study tries to identify the livelihood practices of the char dwellers. It also focus to assess their economic condition in relation to livelihood practices. The research has been conducted through interdisciplinary approach. Different socio technical tools are used to analyze the problem. Local people’s participation in the research process has ensured by using Participatory Rural Appraisal (PRA) tools. The total population is 969 among them 478 are male and 481 are female and about 215 households live in the Char Konabari of which about 60 percent people are engaged in handloom activities as labor as their main source of livelihood. Agriculture is the second highest and about 20 percent people are engaged in such practice; about four percent people are engaged in small business (broker, small retailer) and rests others are engaged in day labor activities and others like van driver etc. The total numbers of employed people of Char Konabari is 267. Out of them only 54 people engaged with farming activities and others are involved with non-farming activities. One-fourth of the total employed person earned the two-third of the total yearly income of the village and remaining four-fifth employed person earned only one-third of the total yearly income. On the other hand about 586 households live in Dakhin Boro-char of which about 60% and 30% people are agricultural farmer and fishermen. On-farm activities are dominant in Dakhin Boro-char. Most of the farmers have their own land as well as they also cultivate khas (public) land. The rest of the people are engaged in day labor activities, petty business and others (boatsmen). Cultivated land, Domestic animal, grazing land and wet land are the major natural resources of Dakhin Boro-char. The total numbers of employed people of Dakhin Boro-char are 598 and most of them are engaged in agricultural and fisheries activities. The per capita income of the Char Konabari and Dakhin Boro-char is about US$0.54 and US$0.87 respectively. Although women are involved in livestock rearing, their contribution did not recognized socially and economically. Keywords: Livelihood; Resource; Char dwellers; Char Stability; Interdisciplinary. DOI: 10.3329/jbayr.v1i1.6838 Journal of Bangladesh Association of Young Researchers Vol.1(1) 2011 pp.15-30